Relationship Between Disease Activity, Levels of IFN-a, IL-4, IL-6, and Anti-NMDA to Cognitive Dysfunction (MoCA-INA Score) in Systemic Lupus Erythematosus (SLE) Patients with Cognitive Dysfunction - Bantar Suntoko; Suharyo Hadisaputro; Handono Kalim; Suyanto Hadi; Wahyu Adirama Saputra (Acta Medica Indonesiana, 2023)
Background: Neuropsychiatric Systemic Lupus Erythematosus (NPSLE) is a condition that impacts the patients’ brain with SLE, and cognitive dysfunction (CD) is the most common manifestation. Subsequently, the CD hurts the life quality of SLE patients and creates impaired social function. Furthermore, the Montreal Cognitive Assessment (MoCA-INA) is a screening instrument to evaluate cognitive function. In the context of lupus, cytokines, and autoantibodies act as biomarkers in SLE disease control activities. Purpose: The aim of this study was to analyze the correlation between disease activity, IFN-a, IL-4, IL-6 and Anti-NMDA on CD (MoCA-INA Score) in SLE patients with CD. Methods: This analytical observational study was performed with a cross-sectional design and included a sample of 56 SLE patients. The independent variables were the degree of the disease activity, and levels of IFN-a, IL-4, IL-6, and anti-NMDA. The dependent variable consisted of the degree of CD (MoCA-INA score), while the confounding variables were age, DM, gender, hypertension, obesity, and dyslipidemia. Subsequently, the CD was described as a MoCA-INA score <26, and disease activity was estimated based on the SLEDAI score. Results: Increased IL-6 levels were correlated with decreased MoCA-INA scores (p=0.003; r= -0.387). Younger age was found to be associated with more severe CD (p=0.006) Conclusion:In conclusion, IL-6 levels can be used as a predictor severity of CD in SLE patients.